NICARDIPINE REDUCES THE LEVELS OF LEUKOTRIENE-C4 AND PROSTAGLANDIN-E2, FOLLOWING DIFFERENT ISCHEMIC PERIODS IN RAT-BRAIN TISSUE - YEGEN, BERRAK (CHURCHILL LIVINGSTONE, 1992)
Ischemic depolarization of nerve membranes is associated with a rapid influx of calcium into the cell, resulting in production of arachidonic acid (AA) metabolites. These metabolites, particularly leukotriene C4 (LTC4) have a very potent vasoconstrictor effect on cerebral arteries inducing vasogenic edema that may damage the ischemic penumbra. Calcium antagonists are assumed to prevent or reduce metabolic disturbances associated with ischemia. In this study, after developing an experimental animal model simulating the concept of the ischemic penumbra in the rat, the levels of LTC4 and prostaglandin E2 (PGE2) produced in the forebrain following different ischemic periods, such as 4th, 15th, 60th and 240th min were measured by a bioassay method, including 6 rats for each ischemic group. Then the effect of the 1-4 dihydropirine nicardipine (1 mg/kg) on these mediators was investigated by giving it to the rat 30 min before the development of the ischemic model in each corresponding group (n = 6). We showed that nicardipine significantly reduced the high levels of LTC4 and PGE2 in the 4th min and 4th h of cerebral ischemia (p < 0.005, p < 0.0005). So it may be concluded that institution of nicardipine may be helpful in protecting the ischemic penumbra during the early hours of cerebral ischemia.
Keywords: CEREBROVASCULAR-DISEASE; CEREBRAL-ISCHEMIA; GERBIL BRAIN; CALCIUM; REPERFUSION; EDEMA; ANTAGONISTS; DAMAGE; MODEL; ACID